Pembatasan Hak-Hak Tersangka dan Terdakwa dalam Tindak Pidana Narkoba: Keseimbangan antara Kepentingan Negara dan Hak Asasi Manusia - Ichwan Setiawan; Ridho Fitriantoro; Ibnu Mubarok (LPPM Iblam School of Law, 2024)
Drug abuse has become a crucial issue with pervasive impacts across various sectors, including social, economic, and health. In Indonesia, this problem is increasingly pressing, marked by a surge in the prevalence of abuse, especially among students and teenagers. Although the government has established various policies and regulations through Law No. 35 of 2009, its implementation often sparks controversies related to human rights violations. This journal focuses on the dynamics and challenges in enforcing narcotics criminal law while maintaining human rights protection. Through a normative approach and qualitative analysis, this research examines to what extent public interests and individual rights can be balanced. The findings suggest that this balance requires a comprehensive approach that encompasses legal analysis, alternative sanctions like rehabilitation, and effective oversight mechanisms. These results underscore the need for a more holistic strategy in addressing the drug issue in Indonesia.